2014
DOI: 10.2500/ajra.2014.28.4106
|View full text |Cite
|
Sign up to set email alerts
|

Self-cross-linked Hyaluronic Acid Hydrogel in Ethmoidectomy: A Randomized, Controlled Trial

Abstract: Self-cross-linked HA hydrogel provides superior wound healing to CMC after ethmoidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Self-cross-linked HA demonstrated the ability to facilitate mucocillary regeneration. 21 In this study, 90.2% of the patients (74/82) in the HA hydrogel group had epithelial mucosa lining the ostia, which was higher than that in the control group (70.9%, 56/79) at the 2-week follow-up. The success rate of ostial patency reached 91.5% (75/82) in the HA hydrogel group, as opposed to the control group 77.2% (61/79).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Self-cross-linked HA demonstrated the ability to facilitate mucocillary regeneration. 21 In this study, 90.2% of the patients (74/82) in the HA hydrogel group had epithelial mucosa lining the ostia, which was higher than that in the control group (70.9%, 56/79) at the 2-week follow-up. The success rate of ostial patency reached 91.5% (75/82) in the HA hydrogel group, as opposed to the control group 77.2% (61/79).…”
Section: Discussionmentioning
confidence: 50%
“…It was reported that the synechiae was significantly less in the self-cross-linked HA group than in the Stammberger group. Self-cross-linked HA demonstrated the ability to facilitate mucocillary regeneration 21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded this practice can be appropriate in selected cases. Lastly, Matheny et al 9 report their findings from a randomized clinical trial evaluating use of hyaluronic acid gel versus carboxymethylcellulose after sinus surgery. The hyaluronic acid was associated with more optimal healing at the end of the 12 week potoperative period.…”
mentioning
confidence: 99%